Analysis of Scientific Attitudes of Students on Biology Subject - Sofia Candrikaningtyas; Nurul Hidayati Utami; Siti Sarah (Universitas Lambung Mangkurat, 2023)
Scientific attitudes are possessed by each student who engages in scientific works, including communication and observation. Scientific attitudes training and application in biology learning are required in order to internalize. Biology is one of the senior high school school subjects in which students are expected to acquire a comprehensive understanding of the subject by comprehending and applying its fundamental concepts and principles to other disciplines. The purpose of this research is to describe the scientific attitude of students of X grades at SMAN 1 Daha Utara, with a particular focus on biology. This is a quantitative study employing a descriptive methodology and a validated questionnaire for data collection. The data collection was conducted via random sampling. Class X students of SMA Daha Utara during the 2022-2023 academic year constitute the population. The research instrument utilized is based on the scientific attitude instrument for biology learning. On the basis of the collected data, it was determined that the scientific attitude of the X grade students at SMAN 1 Daha Utara regarding biology was classified as moderate. The aspects of scientific attitude incorporated in data collection were inquisitive attitude, respect for data/facts, critical thinking, discovery, and perseverance. In biology class, experiential learning activities such as demonstrations and practicums can assist students in internalizing scientific attitudes.